Phenomenon of words migration from English to Polish (using the example of new Internet’s vocabulary) - Kacperska, Beata (Migracja w języku, literaturze i kulturze, 2020)
Polish Internet’s lexis is one of those areas where there is a strong tendency to migrate language elements. Users of social media, messengers or auction sites eagerly borrow words of English to Polish and then absorb and disseminate it in everyday speech. On the basis of the collected research material (mainly new non-personal nouns), the article shows the trends that can be seen in the reception and assimilation of new words thematically related to the internet. Attention was paid to such elements as their word-formation and variability of spelling. Then on the similarity of dictionary entries describes two nouns borrowings: selfie and clickbait.